Identification of Human Resources in the Application of SME Technology - Sulistyan, Riza Bahtiar; Carito, Danang Wikan; Cahyaningati, Retno; Taufik, Mokhamad; Kasno, Kasno; Samsuranto, Samsuranto (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
Small and Medium Enterprises (SMEs) are required to keep up with technological developments. However, in its implementation there are still many obstacles that occur. The purpose of this study is to identify the obstacles that occur for SMEs in implementing technology. This research uses a case study approach by conducting a more in-depth investigation. A total of 396 SMEs identified the obstacles in the application of technology. The results showed that the obstacles found were in the form of factors from owners who did not understand or follow technological developments, age factors, education levels, online promotions were not maximized, few customers, few types of goods, competition, and relatively short age of goods. Technological developments are applied more to the sales system that is carried out online. The main obstacle is the human resource factor owned by business actors, so it must really be overcome to increase the competence of its human resources